EVALUASI KINERJA KERJA MAHASISWA PARIWISATA DI INDUSTRI PARIWISATA PULAU LOMBOK - Rizal Kurniansah (Jurnal Ilmiah Hospitality, 2019)
Response to the success or failure of the company's objectives. Therefore, corporate leaders must consider or evaluate the performance of the work of employees to the ability of an employee continue to rise. This study aims to find out about the job performance of students on the job training Academy of Tourism Mataram in Lombok island hospitality industry. Data collection techniques using the method of observation, literature study and questionnaire. The sampling technique used sampling purposive with a sample size of 20 people. Analysis of the data used in this research is descriptive qualitative and quantitative analysis. Based on the results of research conducted that the work performance of students on the job training is satisfactory with an average indicator value totaling 81.78 (Table 3.8). Although each indicator has an average value that is satisfactory, there are indicators that have low values are indicators of leadership with the index 73. When referring to the three-box method, the value of this index is still in the high category, that is to say, the performance of students on the job training is quite satisfactory in terms of leadership. But when compared with other indicators, the index value indicator of leadership (73) is still far from the maximum index value in the indicator element of cooperation (91), so it needs to be given special attention so that the job performance of students on the job training Academy of Tourism Mataram will run maximum.